Magnesium extraction of ferronickel slag processed by alkali fusion and hydrochloric acid leaching - Prasetyo A.B.; Khaerul A.; Mayangsari W.; Febriana E.; Maksum A.; Andinie J.; Firdiyono F.; Soedarsono J.W. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A research using ferronickel slag, the by-product of ferronickel production, as raw material for magnesium extraction was carried out. It is essential to upgrade the value of ferronickel slag instead of used directly for reclamation materials. Moreover, the accumulation due to increasing ferronickel demand as well as the environmental contamination due to various potentially toxic elements contained in the ferronickel slag could be prevented. The general objective of this study is to utilize the ferronickel slag for magnesium materials. The specific objective is to determine the optimum conditions of magnesium extraction in the process of alkali fusion followed by hydrochloric acid leaching. A novel method for magnesium extraction from ferronickel slag was carried out through reducing silica content followed by acid leaching method. Alkali fusion of the mixture of ferronickel slag and Na2CO3 at 1000°C for 60 minutes, followed by water leaching at 100°C for 60 minutes with solid to liquid percentage of 20 % was carried out to separate the silica. The leaching residue resulted from water leaching was then leached using hydrochloric acid solution to extract magnesium. The leaching temperature and time as well as the hycrochloric acid concentration were varied in the acid leaching process. Alkali fusion process proved the sodium silicate can be generated and that it can be separated in the water leaching to the leached solution. Meanwhile, the leaching residue was leached using hydrochloric acid to extract the magnesium. The highest magnesium extraction percentage is 82.67% that resulted from an optimum acid leaching condition with temperature of 80°C for 30 minutes using 2M HCl solution. Based on the kinetics study, the activation energy (Ea) for the leaching reaction of magnesium at atmospheric pressure between 32°C to 80°C is 9.44 kJ/mol and affected by diffusion and chemical reactions.